The Idea of the Bottom-Up Paradigm to Top-Down in Regional Arrangement in Indonesia - Mexsasai Indra; Geofani Milthree Saragih; Dessy Artina; Mohd. Yusuf DM; Ahmad Gelora Mahardika (Jurnal Hukum, 2024)
The reformation era in Indonesia emphasized regional autonomy, resulting in the creation of numerous regions, as affirmed by Articles 18, 18A, and 18B of the 1945 Constitution. Laws Number 22 of 1999 and 23 of 2014 supported a bottom-up paradigm, allowing local communities to propose new regions. However, not all proposals were accepted by the central government, leading to national integration threats and community conflicts. This approach has resulted in unequal development and delays due to conflicting interests between local communities and the central government. Such imbalances have fostered resentment and hindered cohesive national development. This research proposes a top-down approach where the central government fully oversees regional expansion. By centralizing the decision-making process, resources and development opportunities can be more evenly distributed, reducing conflicts and streamlining administrative procedures. The urgency of this shift is underscored by the potential risks to national unity and stability under the current system. The proposed top-down approach aims to enhance the efficiency and effectiveness of state administration, ensuring that regional autonomy contributes positively to national cohesion and progress.